(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Good Company Culture, Company Policies, Convenient Work location, Communication, job satisfaction, opportunities for promotion and career prospects, fair salary are few area which are critically important from the view point of most of the employees. The main objective is to study about the Emotional Intelligence and how the Emotions of employees have an impact on the Employee Performance. For this purpose a sample of 150 was collected from the employees and percentage analysis, factor analysis, Kruskall Wallis test and one way Anova were used as tools to analyze the data. The study is descriptive in nature and the study reveals that ther is significant relationship between employees Emotional Intelligent and Employee Performance. The study revealed that there is significant relationship between Employees Emotional Intelligence and their performance. Emotional Intelligence accounted for about 31% of Employees performance.